(untitled) (KYAMC Journal, 2022)
Endometriosis affecting the skin is a very much rare surgical entity encountered almost exclusively in women of childbearing age. It commonly presents as a discoloring painful cutaneous swelling, the pain being most commonly a cyclical one occurring during menstrual bleeding. It often needs histopathological examination to arrive at a correct diagnosis. Otherwise, the diagnosis is usually presumptive from typical and atypical presentations and other supportive imaging investigations. Wide surgical excision is the gold standard curative treatment of choice. Nonsurgical treatment includes use of such hormonal agents as danazol or leuprolide, oral contraceptive pills, etc. which can’t definitely cure the patient from this nonfatal ailing disease. All other examples of benign and malignant cutaneous swellings like desmoid tumors, fibro-histiocytoma, dermatofibroma protuberans, papilloma, melanoma, visceral malignancies and many other types of fibromatosis are to be included in the differential diagnosis. These patients with cutaneous endometriosis need to be additionally evaluated for endometriosis elsewhere in the body especially in the pelvis and the abdomen proper, though no other tissue like brain, lungs, liver etc. are not immune to it. In women of childbearing age with abdominal or pelvic wall masses or an area of soft-tissue thickening at cross-sectional imaging in or very close to previous surgical scars, endometriosis is to be strongly suspected by the consulting radiologist. Imaging investigations like CT, USG, and especially, MRI may help in the diagnosis of scar endometriosis, but it is only the biopsy that is definitely confirmatory. KYAMC Journal. 2022;12(04): 243-249